#include
int main()
{
int num;
scanf("%d", &num);
printf("%d", num*num);
return 0;
}
![2y^2\,\mathrm dx-(x+y)^2\,\mathrm dy=0](https://tex.z-dn.net/?f=2y%5E2%5C%2C%5Cmathrm%20dx-%28x%2By%29%5E2%5C%2C%5Cmathrm%20dy%3D0)
Divide both sides by
to get
![2\left(\dfrac yx\right)^2-\left(1+\dfrac yx\right)^2\dfrac{\mathrm dy}{\mathrm dx}=0](https://tex.z-dn.net/?f=2%5Cleft%28%5Cdfrac%20yx%5Cright%29%5E2-%5Cleft%281%2B%5Cdfrac%20yx%5Cright%29%5E2%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D0)
![\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{2\left(\frac yx\right)^2}{\left(1+\frac yx\right)^2}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B2%5Cleft%28%5Cfrac%20yx%5Cright%29%5E2%7D%7B%5Cleft%281%2B%5Cfrac%20yx%5Cright%29%5E2%7D)
Substitute
, so that
. Then
![x\dfrac{\mathrm dv}{\mathrm dx}+v=\dfrac{2v^2}{(1+v)^2}](https://tex.z-dn.net/?f=x%5Cdfrac%7B%5Cmathrm%20dv%7D%7B%5Cmathrm%20dx%7D%2Bv%3D%5Cdfrac%7B2v%5E2%7D%7B%281%2Bv%29%5E2%7D)
![x\dfrac{\mathrm dv}{\mathrm dx}=\dfrac{2v^2-v(1+v)^2}{(1+v)^2}](https://tex.z-dn.net/?f=x%5Cdfrac%7B%5Cmathrm%20dv%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B2v%5E2-v%281%2Bv%29%5E2%7D%7B%281%2Bv%29%5E2%7D)
![x\dfrac{\mathrm dv}{\mathrm dx}=-\dfrac{v(1+v^2)}{(1+v)^2}](https://tex.z-dn.net/?f=x%5Cdfrac%7B%5Cmathrm%20dv%7D%7B%5Cmathrm%20dx%7D%3D-%5Cdfrac%7Bv%281%2Bv%5E2%29%7D%7B%281%2Bv%29%5E2%7D)
The remaining ODE is separable. Separating the variables gives
![\dfrac{(1+v)^2}{v(1+v^2)}\,\mathrm dv=-\dfrac{\mathrm dx}x](https://tex.z-dn.net/?f=%5Cdfrac%7B%281%2Bv%29%5E2%7D%7Bv%281%2Bv%5E2%29%7D%5C%2C%5Cmathrm%20dv%3D-%5Cdfrac%7B%5Cmathrm%20dx%7Dx)
Integrate both sides. On the left, split up the integrand into partial fractions.
![\dfrac{(1+v)^2}{v(1+v^2)}=\dfrac{v^2+2v+1}{v(v^2+1)}=\dfrac av+\dfrac{bv+c}{v^2+1}](https://tex.z-dn.net/?f=%5Cdfrac%7B%281%2Bv%29%5E2%7D%7Bv%281%2Bv%5E2%29%7D%3D%5Cdfrac%7Bv%5E2%2B2v%2B1%7D%7Bv%28v%5E2%2B1%29%7D%3D%5Cdfrac%20av%2B%5Cdfrac%7Bbv%2Bc%7D%7Bv%5E2%2B1%7D)
![\implies v^2+2v+1=a(v^2+1)+(bv+c)v](https://tex.z-dn.net/?f=%5Cimplies%20v%5E2%2B2v%2B1%3Da%28v%5E2%2B1%29%2B%28bv%2Bc%29v)
![\implies v^2+2v+1=(a+b)v^2+cv+a](https://tex.z-dn.net/?f=%5Cimplies%20v%5E2%2B2v%2B1%3D%28a%2Bb%29v%5E2%2Bcv%2Ba)
![\implies a=1,b=0,c=2](https://tex.z-dn.net/?f=%5Cimplies%20a%3D1%2Cb%3D0%2Cc%3D2)
Then
![\displaystyle\int\frac{(1+v)^2}{v(1+v^2)}\,\mathrm dv=\int\left(\frac1v+\frac2{v^2+1}\right)\,\mathrm dv=\ln|v|+2\tan^{-1}v](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint%5Cfrac%7B%281%2Bv%29%5E2%7D%7Bv%281%2Bv%5E2%29%7D%5C%2C%5Cmathrm%20dv%3D%5Cint%5Cleft%28%5Cfrac1v%2B%5Cfrac2%7Bv%5E2%2B1%7D%5Cright%29%5C%2C%5Cmathrm%20dv%3D%5Cln%7Cv%7C%2B2%5Ctan%5E%7B-1%7Dv)
On the right, we have
![\displaystyle-\int\frac{\mathrm dx}x=-\ln|x|+C](https://tex.z-dn.net/?f=%5Cdisplaystyle-%5Cint%5Cfrac%7B%5Cmathrm%20dx%7Dx%3D-%5Cln%7Cx%7C%2BC)
Solving for
explicitly is unlikely to succeed, so we leave the solution in implicit form,
![\ln|v(x)|+2\tan^{-1}v(x)=-\ln|x|+C](https://tex.z-dn.net/?f=%5Cln%7Cv%28x%29%7C%2B2%5Ctan%5E%7B-1%7Dv%28x%29%3D-%5Cln%7Cx%7C%2BC)
and finally solve in terms of
by replacing
:
![\ln\left|\frac{y(x)}x\right|+2\tan^{-1}\dfrac{y(x)}x=-\ln|x|+C](https://tex.z-dn.net/?f=%5Cln%5Cleft%7C%5Cfrac%7By%28x%29%7Dx%5Cright%7C%2B2%5Ctan%5E%7B-1%7D%5Cdfrac%7By%28x%29%7Dx%3D-%5Cln%7Cx%7C%2BC)
![\ln|y(x)|-\ln|x|+2\tan^{-1}\dfrac{y(x)}x=-\ln|x|+C](https://tex.z-dn.net/?f=%5Cln%7Cy%28x%29%7C-%5Cln%7Cx%7C%2B2%5Ctan%5E%7B-1%7D%5Cdfrac%7By%28x%29%7Dx%3D-%5Cln%7Cx%7C%2BC)
![\boxed{\ln|y(x)|+2\tan^{-1}\dfrac{y(x)}x=C}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cln%7Cy%28x%29%7C%2B2%5Ctan%5E%7B-1%7D%5Cdfrac%7By%28x%29%7Dx%3DC%7D)
Answer:
5cm^3
Step-by-step explanation: please let me know if that wrong.
A) 18x2 = 36
hope I helped
Best of luck :)